2015
DOI: 10.1103/physrevb.92.024505
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiotheory of superconductivity in a magnetic field. I. Spin density functional theory for superconductors and Eliashberg equations

Abstract: We present a first-principles approach to describe magnetic and superconducting systems and the phenomena of competition between these electronic effects. We develop a density functional theory: SpinSCDFT, by extending the Hohenberg-Kohn theorem and constructing the non-interacting KohnSham system. An exchange-correlation functional for SpinSCDFT is derived from the Sham Schlüter connection between the SpinSCDFT Kohn-Sham and a self-energy in Eliashberg approximation. The reference Eliashberg equations for sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
(96 reference statements)
0
21
0
Order By: Relevance
“…On the other hand, it has been shown that SCDFT does not work for nitride superconductors, alkali‐doped fullerides, etc., suggesting that we have to go beyond the standard ME theory to understand superconductivity in these compounds. Thus development of F xc applicable not only to the conventional phonon mechanism but also to other unconventional mechanism is an interesting and exciting challenge …”
Section: Under High Pressuresmentioning
confidence: 99%
“…On the other hand, it has been shown that SCDFT does not work for nitride superconductors, alkali‐doped fullerides, etc., suggesting that we have to go beyond the standard ME theory to understand superconductivity in these compounds. Thus development of F xc applicable not only to the conventional phonon mechanism but also to other unconventional mechanism is an interesting and exciting challenge …”
Section: Under High Pressuresmentioning
confidence: 99%
“…Although gap anisotropy analysis is present in such codes, much of the DFT based ab initio work focused on other aspects. These aspects being; expanding the description of s-wave superconductivity with emphasis on the correct description of the driving mechanism [20][21][22][23][24], or on the extension to unconventional pairing pushing the boundaries in our treatment of iron based [25], spin [26] and magnetic effects [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…large effort to develop the theoretical framework into a fully functioning method, investigating functionals [39][40][41][42], extensions [43][44][45][46] and transforming it into a useful and predictive tool in material science [23,[47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%